Modulation of inflammatory signaling and cytokine release from microglia by celastrol incorporated into dendrimer nanocarriers. (August 2012) - Boridy, Sebastien; Soliman, Ghareb M; Maysinger, Dusica
Aim: This study investigates the capacity of a potent anti-inflammatory nanomedicine, celastrol, incorporated into poly(amidoamine) dendrimers, to inhibit endotoxin-mediated signaling in microglia.Materials & methods: Celastrol was incorporated into amino (Cel/G4-NH2 ) and hydroxyl (Cel/G4-OH) terminus poly(amidoamine) (G4) dendrimers. Cell viability, release of nitric oxide, IL-6, TNF-α and activation of MAPK (e.g., p38 and JNK) and NF-κB were assessed in endotoxin (i.e., lipopolysaccharide) stimulated microglial cells.Results: G4-OH and G4-NH2 increased celastrol aqueous solubility by seven- and 12-fold, respectively. G4-OH and Cel/G4-OH suppressed lipopolysaccharide-mediated release of proinflammatory mediators, such as nitric oxide and IL-6, but not TNF-α, without reducing microglial cell viability, while Cel/G4-NH2 potentiated cytotoxicity and cytokine release. Blockade of proinflammatory signaling was accompanied by attenuation of p38 MAPK activation.Conclusion: This study supports the potential use of poly(amidoamine) dendrimers for effective anti-inflammatory therapy in the chronically inflamed CNS. Original submitted 22 July 2011; Revised submitted 8 December 2011; Published online 4 April 2012